Channel catfish granzyme-like I is a highly specific serine protease with metase activity that is expressed by fish NK-like cells. (October 2016) - Thorpe, Michael; Akula, Srinivas; Hellman, Lars
Abstract: Here we present the extended cleavage specificity of catfish granzyme-like I, previously identified in fish NK-like cells. This protease has been characterised using substrate phage display and further validated by using a panel of recombinant substrates. A strict preference for Met in the P1 (cleavage) position, indicating metase specificity was observed. A screening of potential in vivo substrates was performed based on the derived P5-P3′ consensus: Arg-Val-Thr-Gly-Met ↓ Ser-Leu-Val. Channel catfish caspase 6 was one very interesting potential target identified. This site was present in an adjacent position to the classic caspase activation site (Asp179 in human caspase 6). Cleavage of this site (hence potential activation) by the catfish granzyme-like I could reveal a novel mechanism of caspase 6 activation. This poses an interesting idea that the role of granzyme-like proteases in the activation of caspase dependent apoptosis mechanisms has been conserved for over 400 million years. Highlights: The primary and extended cleavage specificity of a catfish NK cell protease. A highly specific met-ase. The most specific hematopoietic serine protease so far characterised in any species. A potential target is caspase 6 indicating a role in apoptosis induction.